Determination of the Benoa Bay Maritime Conservation Area in the Effectiveness of Environmental Maintenance - Mega Rasnawati; Putu Gede Arya Sumerta Yasa (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2021)
Reclamation based on the revitalization of Benoa Bay-Bali which is regulated in Presidential Decree No. 51 of 2014 has the goal of increasing competitiveness in the field of tourism destinations. However, many Balinese people reject the reclamation of Benoa Bay-Bali because the Benoa Bay area is a conservation area. With various objections from the Balinese people, KEPMEN KP No: 46/ KEPMEN-KP/2019 was issued regarding the management of the maritime cultural protection area of ??Benoa Bay-Bali by appointing the Bali Provincial Government as the manager. This study aims to examine policies regarding the maritime conservation area of ??Benoa Bay-Bali managed by the Provincial Government of Bali, as well as the determination of the Benoa Bay-Bali maritime conservation area to function effectively in the framework of environmental preservation. Using sociolegal research with a statutory approach and a case approach. The result of the research is that there is no further regulation regarding the Bali Provincial Regulation regarding the management of the Benoa Bay maritime conservation area, so that there is a norm vacuum. It is hoped that the determination of the Benoa Bay maritime conservation area to be able to effectively provide a positive impact in environmental maintenance activities, in which to ensure its wise use and increase the quality of its value and diversity.